The moderator effect of personality traits on performance appraisal effectiveness - Muhammad Ishaq, Hafiz (2013)
The performance appraisals systems constitute an integral part of any career development process. Many organizations are facing problems regarding their performance appraisal systems. The main goal of the current research is to determine the moderating role of 5 Big Personality Traits in relation to performance appraisal systems and their effectiveness. The study adopted a quantitative approach using self-administered questionnaires. The Systemic Justice Scales to study the performance of employees and effectiveness of appraisals, and Big Five Inventory for moderating variables were used to identify the role of personality in the performance appraisal system. The present study based on convenience sampling was conducted on 706 employees of a Commercial Banking Sector in Pakistan. Linear and moderated regressions analyses were conducted to examine straight and moderated relationships. The findings from the study indicated that there is a significant relationship between perceived fairness, appraisal satisfaction and elimination of rating errors with effectiveness of performance appraisal. On the contrary, personality traits as a moderator revealed that extraversion and conscientiousness exhibit a significant moderating role between appraisal satisfaction, performance feedback and effectiveness of performance appraisal. Besides that, the results showed that the conscientiousness does moderate the relationship between appraisal satisfaction, elimination of rating errors and effectiveness of performance. Another moderator, openness to experience shows that it has a significant moderating role between elimination of rating error and effectiveness of performance. Guidelines are provided and recommended to human resource practitioners, academicians and researchers to consider personality during the process of performance appraisal in organizations for the improvement of effectiveness in performance appraisal processes.